Sports Policing Tools in a Changing World - Tóth, Nikolett Ágnes (Magyar Rendészet, 2018)
Based on the research into the relationship between sport and policing we can say that sports policing is a specific part of sports administration. The paper seeks answers to the following questions: What are the reasons for football hooliganism? What previous events, stadium disasters have happened in the last few decades that focussed the attention of those concerned with securing events on the fact that the established practice needed to be changed and new legal norms had to be established? Lord Justice Peter Taylor was the first to point out all these issues, after, in co-operation with a committee, he had conducted a detailed analysis of the problems. His proposals radically changed the image of both modern British and European soccer, as well as the related Hungarian rules and regulations.